(untitled) (Research, Society and Development, 2022)
The Overlap Syndrome (OS) associated with Systemic Lupus Erythematosus (SLE) and Lichen Planus (LP), a rare entity, is characterized by a clinical and immunohistopathological signs of both. We report the case of a 39-year-old female patient diagnosed with SLE, presenting with intraoral lesions whose diagnostic hypotheses were Oral Lichen Planus (OLP) and SLE. In this scenario, the present study aimed to describe the pathologies mentioned, as well as to expose the difficulties of the diagnostic process of the overlap syndrome in question, explaining the stages of the disease and the treatment performed. The work was carried out through a case study with descriptive objectives and a qualitative approach using clinical knowledge of dermatology, stomatology and rheumatology, based on bibliographic research and integrative literature review in digital databases with the analysis of complementary, histopathological and immunofluorescence exams. In the biopsy of clinically ambiguous lesions, as in the case of the patient’s oral lesions, histopathological features of one or both processes can be found simultaneously or fluctuating at different times, making diagnosis difficult and complicating prognosis and treatment. Thus, it was observed that direct immunofluorescence (DIF) has become an essential tool to aid in the diagnosis of this condition. This case reinforces that OS has a challenging diagnosis and its treatment involves several professionals to manage it.